Perancangan Alat Pengatur Jarak Pengunjung Museum Menggunakan Sensor Ultrasonik Berbasis Mikrokontroler At89s51 - Eko Setia Budi; Raden Bagus Dimas Putera; Abdul Rahman Kadafi (JURIKOM (Jurnal Riset Komputer), 2019)
In the current era of globalization, the rapid advance of information technology. The computer is the equipment created to facilitate human work, while achieving good progress in the manufacture of hardware or software. For that I am as a writer tries Final for the manufacture of a tool called "Distance Visitor Management Tool Museum Using Ultrasonic Sensor Based on Microcontroller AT89S51". This tool serves as a detector or a spacer visitors with tools or objects that want to be protected. With this tool would facilitate the security officer on duty, can more easily determine if there is someone who intentionally or unintentionally cross the line that has been determined the authorities to look at the tools or objects protected. For that here I try to practice and make this tool as a pilot and as inspirational. The design of this tool is very fit and have a good solution to help get the data without having to calculate and remember in mind manually.